Chromosome number in South American species of Bothriochloa (Poaceae: Andropogoneae) and evolutionary history of the genus - Scrivanti, Lidia Raquel (2010)
Mitotic chromosome number of 14 taxa of Bothriochloa native to Argentina, Brazil and Uruguay were surveyed. Chromosome numbers of B. eurylemma, B. meridionalis and B. velutina are reported for the first time, with 2n = 6x = 60, and this ploidy level is the most common among the studied taxa. In addition, new cytotypes were found for B. alta (2n = 60), B. barbinodis (2n = 60), B. exaristata (2n = 80), B. laguroides var. torreyana (2n = 80), B. longipaniculata (2n = 60 and 80), B. perforata (2n = 60) and B. springfieldii (2n = 60). These numbers differ from those reported in the literature.